Guidance on Poetry Writing 11th Grade Students of SMA PGRI 3 Randudongkal, Pemalang Regency - Mulyono, Tri; Basukiyatno, Basukiyatno; Triana, Leli; Aulia, Afsun; Rofi’udin, Rofi’udin (ASEAN Journal of Empowering Community, 2023)
This community service activity was conducted in Pemalang Regency, Central Java, specifically at SMA PGRI 3 Randudongkal, organized in collaboration between LPPM UPS and the Literary Committee of the Regional Arts Council (DKD) of Pemalang Regency. Students of SMA PGRI 3 Randudongkal have a very high interest in literature but do not yet have the skills to write poetry well. Therefore, this activity is expected to equip them with poetry writing skills. The activities packaged in the form of a workshop not only provide participants with material about poetry but also require them to produce poems to be published in a poetry collection book. The implementation model is Problem Based Learning. (PBL). The method of presentation is lectures, discussions, question and answer sessions, and assignments. This activity is conducted using natural media. It means that the participants are expected to write poems based on what they see around the school environment.